Lameness and Radiological Evaluation of Elastic Plate Osteosynthesis using Veterinary Cuttable Plates for Tibial Fracture Repair in Immature Dogs with and without Platelet Rich Plasma - MS, Rajath; N, Nagaraju; B N, Nagaraja; Murthy K M, Srinivasa; K, Manjunatha; B R, Balappanavar (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The present study was carried out on 12 clinical cases to compare elastic plate osteosynthesis using veterinary cuttable plates for tibial fracture repair in young dogs with and without platelet rich plasma. Young dogs with tibial diaphyseal fractures were randomly divided into two groups: Group A, dogs stabilized with Veterinary Cuttable Plate (VCP) and application of activated Platelet rich plasma (PRP) perioperatively, whereas Group B, stabilized with VCP without application of PRP. Fracture stabilization using VCP provided relative stability, micromotion at the fracture site resulting in secondary bone healing. All the dogs of group A had Grade V lameness preoperatively, showed Grade I lameness by end of 60 days, whereas out of six dogs in group B which had Grade V lameness preoperatively, one dog had Grade II lameness by the end of study period. Radiologically, all dogs of group A and B showed alignment of bone fragments and implants in situ on 1st post-operative day. In group A callus formation was noticed on 30th day and by end of 60th day remodelling was observed with corticomedullary continuity. In group B, varying amount of callus formation was noticed by 45th day and complete bone healing via bridging callus formation by 60th day suggesting complete bone healing. Considering lameness grade and radiological healing during the study period, group A dogs showed marginally early fracture healing, and weight-bearing compared to group B dogs. PRP application accelerated bone healing and improved early limb function.